2006
DOI: 10.3346/jkms.2006.21.4.761
|View full text |Cite
|
Sign up to set email alerts
|

Myxedema Ascites: Case Report and Literature Review

Abstract: Myxedema ascites caused by hypothyroidism is rare, so its diagnosis is often delayed and patients frequently receive unnecessary procedures such as liver biopsies and exploratory laparotomies. We report a 71-yr-old man with clinical ascites that was the first manifestation of hypothyroidism, and which resolved completely in response to thyroid hormone replacement therapy. To our knowledge, this is the first report of myxedema ascites in Korea. A review of the literature revealed 51 well-documented cases of myx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 14 publications
0
25
0
10
Order By: Relevance
“…Decreased hepatic metabolism in hypothyroidism is reflected by reduced oxygen consumption [70] and causes a significant decrease in gluconeogenesis [71] and urea nitrogen production [72] . Myxedema ascites in hypothyroidism is rare and may be a long-standing overlooked and/or isolated sign of the disease [73] . The serum-to-ascites albumin gradient is usually > 1.1 g/dL with a high protein content [4,73] .…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased hepatic metabolism in hypothyroidism is reflected by reduced oxygen consumption [70] and causes a significant decrease in gluconeogenesis [71] and urea nitrogen production [72] . Myxedema ascites in hypothyroidism is rare and may be a long-standing overlooked and/or isolated sign of the disease [73] . The serum-to-ascites albumin gradient is usually > 1.1 g/dL with a high protein content [4,73] .…”
Section: Livermentioning
confidence: 99%
“…Myxedema ascites in hypothyroidism is rare and may be a long-standing overlooked and/or isolated sign of the disease [73] . The serum-to-ascites albumin gradient is usually > 1.1 g/dL with a high protein content [4,73] . Although considered to be the result of hypothyroidism-related chronic right-heart failure [74,75] , it is mainly attributed to increased permeability of vascular endothelium [4,76] .…”
Section: Livermentioning
confidence: 99%
“…Myxedema ascites appear in fewer than 4% of patients with hypothyroidism (3), and are promptly reduced with thyroid hormone replacement according to previous reports (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 90%
“…de Castro et al (10) reported that SAAG values tend to exceed 1.1 g/dL in myxedema ascites based on a review of eight patients, in which only one case presented a gradient less than 1.1 g/dL as was found in our case. Otherwise, ascitic fluid with myxedema has been described as exudates (total protein>2.5 g/dL) in almost all cases, and these disappear rapidly after the start of thyroid hormone replacement (6). Hypothyroidism is assumed to cause an increase in capillary permeability, followed by the escape of protein-rich fluid into the extravascular component and produce ascites with the above-mentioned properties (11).…”
Section: F I G U R E 3 Ch E S T X R a Y O N T H E 1 0 T H H O S P Imentioning
confidence: 99%
“…We assessed the phenomenon of low voltage in patients with ascites and demonstrated that attenuated voltage could be partially corrected if the precordial electrodes were placed one or two intercostal spaces cranially [4] . Having in mind that severe hypothyroidism is associated with ascites [5] and that there was a trend toward lower albumin values in the study by Yamanaka et al [1] , we believe that the presence of ascites should be actively assessed when severely hypothyroid patients are diagnosed with low voltage. As demonstrated in our study, drainage of ascites normalizes the ECG in these patients.…”
mentioning
confidence: 99%